Vascular malformation mimicking multiple sclerosis active plaque: Usefulness of susceptibility weighted imaging (SWI) to perform correct diagnosis. Issue 5 (October 2015) - Marsecano, Claudia; Perri, Marco; Michelini, Giulia; Varrassi, Marco; Splendiani, Alessandra; di Cesare, Ernesto; Masciocchi, Carlo; Gallucci, Massimo
Brain focal hyperdensity areas are common findings in computed tomography examinations, often further evaluated in magnetic resonance imaging exams. These are usually haemosiderin and calcified perivascular clusters known as cerebral microbleeds and may be secondary signs of brain disorders. Cerebral microbleeds are paramagnetic and ferromagnetic substances determining magnetic field inhomogeneity. Susceptibility weighted imaging (SWI) performed at 3T with phase post-processing is very useful in evaluating this field variation. In fact in the past decade SWI has been increasingly reported for its clinical value in adults with neurologic disorders, traumas, arterial venous malformations, occult venous diseases, tumours and functional brain imaging. The occasional computed tomography findings of single or multiple focal hyperdense areas can mimic many of these brain disorders and lead to misinterpretations. For these reason it is useful to have a more detailed diagnosis with MRI brain examination. The authors highlight the role of SWI sequence in the differential diagnosis among active plaque, vascular malformation and haemorrhagic lesion in a case report of a 41-year-old woman suffering from multiple sclerosis with a focal hyperdense area reported in a computed tomography brain examination.